Друковані видання ХХ ст. з історії театрального і музичного мистецтва в колекційному описі акторської сім’ї Бровченків: аналіз, систематизація - Рой, С.В. (Сіверщина в історії України, 2020)
У статті представлені результати дослідження історії театрального і музичного мистецтва першої половини ХХ ст. та включно до середини 1990-х рр. на матеріалах музейної колекції ніжинської акторської сім’ї Бровченко. З’ясовано основні етапи та характер культурно-мистецького (музично-театрального) процесу на теренах України і частково на території колишнього СРСР. This article presents the results of research, history of theater and music in the first half of the twentieth century and mid-1990s, based on materials from the Brovchenko family museum collection. The basic stages and character of the cultural-artistic (musical-theatrical) process in the territory of Ukraine and partly in the territory of the former USSR have been clarified. By their content and functional purpose, the above editions are divided as follows: book, periodical, and reference book. Periodically these stock exhibits are divided into: the interwar 1920–1930, the military, after the war, 1950–70, and 1990. It should be noted that each of the above editions can serve as a primary source for the study of the cultural and artistic process of modernism and the postmodern era, because it allows you to fully trace all the processes of the twentieth century. and until the mid-1990s. All theatrical directors and actors of both Ukraine and the USSR aimed to appeal to the leading classics of Ukrainian and Russian literature, to preserve the artistic and theatrical traditions of both musical and theatrical performances. Confirmation of this thesis are the most famous antitrips and roles of such famous theatrical figures as: Hnat Yura, Terentii Yura, Amvrosii Buchma, Natalia Uzhvi, Ivan Brovchenko, Maria Kryvets (Brovchenko), O. Levada and others. We can find out about them from books and periodicals, brochures, theater programs, booklets and invitations stored in the museum collection of the Brovchenko acting family. Much attention was paid to the teaching methods of theater art and its technique. Postmodern music was counted on as special admirers of classical works to listeners who were close to the music that reflected their present. We learn about this from the programs of the Kyiv Chamber Choir and the Moscow Conservatory named after P.I. Tchaikovskyi, as well as a collection of soldiers’ songs from World War II, dedicated to the liberation of Kyiv, published by A. Stoharenko. Also, Ukrainian variety music was born and developed, the bright representative of which was the alumnus of Maryna Brovchenko, the People’s Artist of Ukraine - Alla Kudlai.